Evaluation on energy efficiency improvement in geothermal power plant with the application of load-based gas removal system and cooling water pump control system - Wibisono Yamin; I.G.B. Ngurah Makertihartha; Jenny Rizkiana (Jurnal Rekayasa Proses, 2020)
Efficient Geothermal Power Plant (GPP) operation can be achieved through the optimum use of steam for turbine and auxiliary (ejectors), and minimum possible condenser pressure for maximum energy conversion in the turbine. In all GPPs, a condenser vacuum is maintained by adequate circulation of cooling water and effective operation of ejectors, which absorb the accumulation of Non-Condensable Gas (NCG), mostly CO2 and H2S, and dispose it to the atmosphere. Typically, GPPs are designed for baseload (100% capacity) operation. Therefore, the performance of supporting equipment such as ejectors and cooling water pumps are not sensitive to load-set fluctuations or changes in NCG content. This fact consequently results in constant parasitic load and ejector's motive steam consumptions. Since 2017 many GPPs in Indonesia have no longer operated at constant full capacity following demand fluctuation, as stated in grid dispatcher's Daily Operating Plan. This condition brings up energy efficiency opportunity to reduce steam and electricity own use through modification or installation of the load-following controller in the ejector system and cooling water pumps. The study aimed to identify the best alternative in devising this adaptive feature in gas removal and circulating water systems from economic and technical aspects. Evaluation's methodology included the development of GPP process modeling and data validation, setting up an alternative framework, testing of GPP performance for each alternative with the calibrated model, and decision analysis from economic and technical aspects to select the best option. The evaluation showed that the ejector's motive steam flow controller was able to reduce auxiliary steam usage at maximum by 7% (equal to 0.7 MWe). In comparison, the circulation water flow controller with Variable Frequency Drive (VFD) could reduce pumps electricity use by 35% (0.76 MWe). The study results recommended the implementation of a motive steam flow controller over the pump's VFD, considering its economic performance, operation flexibility, and lower execution risk.